2019
DOI: 10.1111/bjhp.12399
|View full text |Cite
|
Sign up to set email alerts
|

Classism and dehumanization in chronic pain: A qualitative study of nurses’ inferences about women of different socio‐economic status

Abstract: Objectives. Class-based dehumanization in health is poorly investigated. Beliefs about social class are often shared across cultures, with people of lower socio-economic status (SES) being typically dehumanized. This study specifically examined how nurses' perceptions of pain patients' SES were associated with (more or less) dehumanizing inferences about their pain and different treatment recommendations.Design. Sequential mixed methods including Similitude Analysis (statistical analysis of qualitative data) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 51 publications
2
42
1
Order By: Relevance
“…Indeed, very few studies have looked at men or older adults as victims of dehumanization, even though older people are more often dehumanized than young people (Boudjemadi, Demoulin, & Bastart, 2017) and men may also be denied humanness (Capozza, Falvo, Trifiletti, & Pagani, 2014; Fasoli et al, 2016). This trend is at odds with most social psychology studies that typically focus on social minority groups, who are at an increased risk of dehumanization (Diniz, Castro, Bousfield, & Bernardes, under review; Haslam, 2006; Haslam & Loughnan, 2014; Haslam & Stratemeyer, 2016; Volpato, Andrighetto, & Baldissarri, 2017). Research has also been typically performed in Anglo-Saxon countries (71.3%), leaving other cultural contexts underexplored.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, very few studies have looked at men or older adults as victims of dehumanization, even though older people are more often dehumanized than young people (Boudjemadi, Demoulin, & Bastart, 2017) and men may also be denied humanness (Capozza, Falvo, Trifiletti, & Pagani, 2014; Fasoli et al, 2016). This trend is at odds with most social psychology studies that typically focus on social minority groups, who are at an increased risk of dehumanization (Diniz, Castro, Bousfield, & Bernardes, under review; Haslam, 2006; Haslam & Loughnan, 2014; Haslam & Stratemeyer, 2016; Volpato, Andrighetto, & Baldissarri, 2017). Research has also been typically performed in Anglo-Saxon countries (71.3%), leaving other cultural contexts underexplored.…”
Section: Discussionmentioning
confidence: 96%
“…To date, almost all qualitative SC research has used some form of thematic analysis (TA), or its close cousin qualitative content analysis (Hsieh & Shannon, 2005), for data analysismost commonly Braun and Clarke's (2006) reflexive TA approach (e.g., Auðardóttir & Rúdólfsdóttir, 2020;Beres et al, 2014;Clarke et al, 2015;Diniz et al, This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Choice Of Analytic Methodsmentioning
confidence: 99%
“…Mixed methods study designs are also possible (Hanson, Creswell, Clark, Petska, & Creswell, 2005). Livingston and Testa (2000), for example, used SC in an experimental design, and Diniz, Castro, Bousfield, and Bernardes (2020) in a sequential mixed methods design. It is important to note that while these elements of qualitative SC may be familiar from quantitative research, they do not result from positivist assumptions.…”
Section: What Qualitative Story Completion Offers Counseling Psycholo...mentioning
confidence: 99%
“…A thorough analysis of the links between PCC, neoliberalism, and inequality would exceed the space of this paper–for example, Pistor and Lachmann (2022) show how law produces inequality as a result of creating capital. The classist assumption that nurses implicitly occupy can decrease access to healthcare intervention, contribute to a lower life expectancy, and reproduce care disparities (Diniz et al, 2020). Diniz et al (2020) looked at how nurses conceptualize patients of different socioeconomic status (SES) and found that while patients with middle SES were depicted mostly with positive (autonomous and communicative), patients with low‐SES were also imagined with dehumanizing traits such as “passive towards pain, with poor future prospects and referred to psychoeducation” (Diniz et al, 2020, p. 152).…”
Section: Who Is the Person In Pccmentioning
confidence: 99%